The Impact of Supply Chain Management for The Innovation Activity Development in Russia: Relevant Issues - N.S. Plaskova; N.A. Prodanova; F.A. Khamkhoeva; O. E. Bashina; S.V. Gus'kov (International Journal of Supply Chain Management, 2020)
Abstract- Innovation activity plays a crucial role in the supply chain and socio-economic development of society, both globally and at the level of individual economic entities. Competent and, as a result, effective management of innovation activities contributes to the satisfaction of the material and intellectual needs of society, provides vital functions of society with fundamentally new benefits and leads to a positive economic effect for the economic entities at the micro, meso, and macro levels. An exploratory case study approach to answer the research questions has been conducted in order to develop a model for innovation management within a supply chain of large manufacturing firm. To study the features of the formation of the innovation activity practice and the current state of innovation activity in the Russia; to identify the causes of technological backwardness of Russia and assess the potential for the development of innovation activity to strengthen the position of the state at the global level.